Digital learning Initiatives, Challenges and Achievement in Higher Education in Nepal Amidst COVID-19 - Ashis Acharya; Srijana Subedi; Narayan Gyawali; Nabaraj Poudyal; Ganesh Lamichhane; Govinda Bastola; Babita Aryal; Bibek Raj Bhattarai; Bikash Adhikari; Rishab Marahatha; Madhabi Bhatta; Mohan Paudel; Niranjan Parajuli (International Journal of Asian Education, 2021)
The COVID-19 pandemic has affected higher education institutions (HEIs) worldwide and reshaped the existing educational system. Due to travel constraints and physical separation, there has been a global shift toward distance learning, and Nepal is no exception. This research intends to assess the practicality of online education by evaluating learners' experiences amidst COVID-19. A cross-sectional study was directed among HEIs students in Nepal using self-structured questionnaires. Our study revealed that 64.6% of the respondents were unsatisfied with online classes. More than half of the respondents (53.4%) use cell phones for online studies. Online education was reported to be unappealing to 28.8% of respondents. Variables such as age group (p = 0.05), enjoying class (p < 0.001), hours spent for an online class in a day (p = 0.05), and period for educational work using an electronic device (p = 0.1) were found significant with satisfaction level using both bivariate test and inferential test of univariate binary logistics regression. The challenges and opportunities encountered among students and faculties are highlighted along with the recommendations for fortifying communication in online-based teaching/learning.